Village Human Resources from the Perspective of Village Development Administration Case Study of Bojong Village, Bungbulang District, Garut Regency - Benni Yandiana; Ade Burhanudin; Sopa Siti Marwah; Mulyaningsih (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
Village development in a decentralization setting requires capable village human resources (HR) to deliver accountable development administration, yet many villages face competency and participation gaps. This study analyzes the roles, challenges, and strengthening strategies for village HR in Bojong Village, Bungbulang District, Garut Regency, using development administration theory on managerial functions and government–community relations. A descriptive qualitative single-case design was employed, based on document analysis (RPJMDes and village research reports) and a literature review; themes were generated through thematic analysis. Results show that although officials actively implement programs, limited technical competence, information-technology mastery, institutional capacity, and facilitation skills weaken planning quality, oversight, and substantive community participation. The discussion positions HR strengthening as a core strategy across the village development cycle, operationalized through continuous training, governance digitalization, and institutional strengthening. Policy recommendations include dedicating village budgets for capacity building, providing mentoring, and scaling village information systems to enhance transparency and responsiveness.  Keywords: Development Administration, Village Human Resources, Village Governance Digitalization